Design multi-stopband laminate acoustic metamaterials for structural-acoustic coupled system. (15th January 2019) - Xiao, X.; He, Z.C.; Li, Eric; Cheng, A.G.
Highlights: The laminate acoustic metamaterials with multi-stopband for structural-acoustic coupled system are proposed. Numerical results reveal that two bandgaps are generated around the absorbers' resonant frequency. The excellent performance of NVH using laminate acoustic metamaterials has been clearly verified. Abstract: This paper designs the laminate acoustic metamaterials with multi-stopband for structural-acoustic coupled system. The laminate acoustic metamaterials are composed of carbon-fiber-reinforced polymer (CFRP) and a periodic array of two degrees of freedom (2-DOF) mass-spring-damper subsystems attached to the laminate. According to the dispersion analysis, two stopbands are observed around the absorbers' resonant frequency. Based on the finite element modeling, the multi-stopband behavior has been confirmed. In addition, the effects of damping of vibration absorbers are discussed in this work. By adding the appropriate damping to the vibration absorbers, the two stop bands can be combined into a wider stopband. Subsequently, the analyses of multi-stopband laminate acoustic metamaterials in the structural–acoustic coupled system are performed. The excellent performance of multi-stopband laminate acoustic metamaterials has been applied to the front panel of vehicle, and the noise of passenger compartment cavity is reduced significantly.